Marketing Strategy of Shredded Fish Cob Products of Bumdes Lagunci in Bahari Tiga Village - Suriadi Suriadi; Rabiyatul Jasiyah; Nurdin P (Media Agribisnis, 2022)
This study aims to determine the internal and external factors that affect the marketing of Shredded Fish Tongkol BUMDES lagunci and internal and external analysis of the marketing strategy of Shredded Fish Tongkol BUMDES lagunci. The data used to find out the factors that influence the marketing of Shredded Cob Fish Products is to conduct an interview with a shredded cob fish maker BUMDES Lagunci. Meanwhile, the marketing strategy using SWOT analysis External factors of the household industry of the BUMDES Lagunci community in Bahari Tiga Village consist of; 1) shredded fish business opportunities that are supported a.) close to raw materials. b) the need for labor is always fulfilled. c) support from the government. d) easy credit access. e) ease of obtaining a business license. 2) the threat of shredded fish business is a) weather or climate change. b) competitors of similar ventures. c) shredded cob fish products are not yet known by the wider community. Marketing strategies used, namely 4P Produck Price Place and Promotion. The internal household factors of BUMDES Lagunci Bahari Tiga Village consist of; 1) the strength of the shredded fish business that is supported a) the existence of partnership cooperation. b) skilled labor. c) affordable product prices d) product excellence (taste and packaging) e) adequate facilities and infrastructure. 2) the weakness of the shredded fish business.